KEBERLANJUTAN SISTEM KETERSEDIAAN BERAS NASIONAL : PENDEKATAN TEKNIK ORDINASI RAP-RICE DENGAN METODA MULTIDIMENSIONAL SCALING (MDS) - Rita Nurmalina (Departemen Agribisnis, FEM-IPB, 2008)
This paper aims to analyze the sustainability of rice availability system at national level, based on sustainability index and status using a Rap-Rice Ordination Technique with Multidimensional Scaling (MDS) Method. This study used primary and secondary data. Result of the MDS analysis Rap-Rice ordinary technique showed that a sustainability index of rice availability system at national level was 64.51, which categorized as sustainable sufficient. Analysis for five dimensions (ecology, economy, socio-culture, institution and technology) showed that a sustainability index of national rice availability system for institution and technology dimensions were relatively high, 91.70 and 77.10, respectively, which felt into good category; the index for ecological and socio-cultural dimensions were 69.64 and 53.74, respectively, categorized as satisfactorily sustainable; and the index for economic dimension was 43.48 which categorized as less sustainable. Results of leverage analysis indicated that 23 out of 60 attributes were sensitivity influential to sustainability of rice availability system. Four attributes from economic dimension as priority to be managed were (1) real wage of farm labor, (2) number of farm households with land holding greater than 0.5 hectares, (3) number of farm labors, and (4) value of Regional GDP.